From sand to power: an examination of the solar energy value chain in the Caribbean. (1st January 2014) - Charles, Don
The Caribbean region possesses some attributes which favour the development of the solar photovoltaic (PV) industry. Despite these advantages, the region has had limited success in the solar industry. There are currently challenges in the industry such as information asymmetry, high upfront installation cost, difficult in attaining financing for both manufacturers and potential customers, and licence restrictions for electricity generation. Policy and government support is needed to create an economically attractive environment for the PV industry. Tax concessions, preferential tariffs, tax exemptions, low-interest loans and infra-structure support are examples of the some policy tools needed to develop the solar PV cluster in the Caribbean.